The Direct Titration of Some Sulfonamide in Tablets - Tan Sip Ie; Poey Seng Buw (Institute for Research and Community Services (LPPM) ITB, 1961)
Telah dilakukan beberapa peniteran beberapa sulfonamide jang banjak dipakai di Indonesia, jakni sulfadiazine, sulfamerazine, sulfamezathine dan sulfisomidine (